Does Obesity Affect Early Results after Coronary Artery Bypass Grafting? - Aithoussa, Mahdi; Atmani, Noureddine; Seghrouchni, Anis; Abdou, Abdessamad; Moutakiallah, Younes; Bamous, Mehdi; Bellouize, Siham; Nya, Fouad; Lakhal, Zouhair; Ghadbane, Abdedaim H.; Elbekkali, Youssef; Boulahya, Abdelatif (Scientific Research, 2017)
Background: The aim of this study was to quantify the effect of obesity on early results after coronary artery bypass grafting (CABG). Methods: A retrospective cohort study of patients underwent isolated CABG from January 2000 through December 2012 was conducted. 586 patients were classified into two groups: Obese (n = 100) BMI ≥ 30 kg/m2 and non-obese (n = 486) BMI ≤ 30kg/m2 . Results: The obese patients included more women (p < 0.01), hypertensives (p = 0.01) and dyslipidemics (p = 0001). The CPB, aortic champ times and number of bypass graft were similar between the groups (p = 0.35, p = 0.51 and p = 0.59 respectively). Also the composite of in-hospital mortality and postoperative complication didn’t differ between the groups. The incidence of perioperative myocardial infarction, and need for inotropic drugs or IABP were significantly less in obese patients (p = 0.028, p = 0.031 and p < 0.01 respectively). Conclusions: The current study showed that obesity is not a risk factor of adverse events after CABG and continuous to give another aspect of the “obesity paradox”
Keywords: Obesity; Coronary Artery Bypass Grafting; Morbidity; Mortality